PROFESYONEL KAYIT STÜDYOLARINDAKİ TONMAİSTERLERİN EĞİTİM DURUMLARI VE MÜZİKSEL ÜRETİME KATKILARI - (:unkn) unknown (My University, 2017)
19. yüzyıl sonlarına doğru ilk ses kayıt çalışmaları ile başlayan süreç, ses kayıt teknolojilerinin gelişmesi ile birlikte günümüze dek büyük aşamalar kat etmiştir. Bu süreçle beraber kayıtları yapan ve dinleyicinin bu kayıtları kaliteli bir şekilde duyabilmesini sağlayan insanlar, ilk defa Almanya’da “tonmaister” olarak adlandırılmışlardır. Daha sonra İngiltere’de “sound engineer” terimi kullanılmıştır. Türkiye’de de tonmayster ya da ses mühendisi kelimeleri benimsenmiştir. Araştırmada yöntem olarak tarama modeli kullanılmıştır. Çalışma grubunu profesyonel kayıt stüdyolarında çalışmakta olan ve alanında önemli çalışmalara imza atmış 30 tonmayster oluşturmaktadır. Türkiye’de kendini yetiştirmiş tonmaysterler bu alana öncülük etmektedirler. Tonmaysterlik eğitimi veren üniversitelerin mezunları da müzik sektöründe önemli işlere imza atmaktadırlar. Ancak hem nicelik hem de nitelik açısından daha ileriye gitmek gerekliliği vardır. Bu anlamda üniversitelerin müzik bölümlerinde, konservatuvarlarda ve hatta eğitim fakülteleri müzik bölümlerinde “Müzik Teknolojileri” ana sanat dalı eğitimi verilmesi önerilmektedir. Tonmayster yetiştiren programlarda teorik bilginin yanı sıra tecrübe kazanmaya yönelik proje çalışmalarına ağırlık verilmesi ve eğitimin uygulamalı temeller üzerine kurulması önerilmektedir.

The process started with the first voice recordings towards the end of the 19th century, and with the development of sound recording technologies, it has gone on a great day by day. The people who made the record with this process and made it possible for the listener to hear these records in good quality were first called “tonmaister” in Germany. Later in England, “sound engineer” was used. In Turkey, the word “tonmayster” or “sound engineer” has been adopted. It is thought that the vast majority of sound engineers, their contributions to musical productions in Turkey have come to a certain point by developing themselves in the music market. Universities have the mission and vision to train qualified and competent graduates in their branches. University education in sound engineering area started too late in Turkey. It is not yet known how universities meet the requirement the needs of sound engineering area. This situation requires keeping new researches in this area. The study group of the research are in consist of 30 sound engineers who have been working at profossional recording studios besides they involved to important projects. A questionnaire developed by researchers was used in the study. The frequencies and percentages of the collected data were analyzed. As a result of research, it has been founded that the universities at this area in Turkey can not supply enough number of graduates for demanding sector of the Country. Also the majority of tonmaisters who trained themselves by experience, still lead the sector. It is expected that more educated and qualified tonmaisters to take place in the sector. It is suggested that the main arts education of “Music Technologies” should be given in the music sections of universities, conservatories and even in departments of music teacher training. The training of tonmaisters should be structured with project-based applications as well as theoretical knowledge.
EDUCATIONAL SITUATIONS OF TONMAISTERS AT PROFESSIONAL RECORDING STUDIOS AND THEIR CONTRIBUTIONS TO MUSICAL PRODUCTIONS
Keywords: Eğitim, Eğitim Araştırmaları; Eğitim, Özel; Müzik